Metabolic and Microbiome Alterations Following the Enrichment of a High-Fat Diet With High Oleic Acid Peanuts Versus the Traditional Peanuts Cultivar in Mice - Anavi-Cohen, Sarit; Zandani, Gil; Tsybina-Shimshilashvili, Nina; Hovav, Ran; Sela, Noa; Nyska, Abraham; Madar, Zecharia (Frontiers in Nutrition, 2022)
A new Israeli-developed peanut cultivar, “Hanoch-Oleic” (HO), uniquely contains enlarged oleic acid contents and was designed to confer additional beneficial effects over the traditional cultivar, “Hanoch” (HN). This work elucidates metabolic changes and microbiota adaptations elicited by HO addition to a high-fat diet (HFD). Male C57BL/6 mice were fed for 18 weeks with a normal diet or a HFD with/without the addition of HN (HFDh) or HO (HFDo). Body-weight did not differ between HFD-fed mice groups, while liver and adipose weight were elevated in the HFDh and HFD groups, respectively. Insulin-sensitivity (IS) was also decreased in these groups, though to a much greater extent in the traditional peanuts-fed group. Modifications in lipids metabolism were evident by the addition of peanuts to a HFD. Liver inflammation seems to return to normal only in HFDh. Peanuts promoted an increase in α-diversity, with HFDo exhibiting changes in the abundance of microbiota that is primarily associated with ameliorated gut health and barrier capacity. In conclusion, the HO cultivar appears to be metabolically superior to the traditional peanut cultivar and was associated with an improved inflammatory state and microbial profile. Nevertheless, IS-negative effects reinforced by peanuts addition, predominantly NH, need to be comprehensively defined.